It will be
(-2)^2+4*(-3)(-3) =40
Answer:
Exact answer is 0.00076232
Step-by-step explanation:
i can give give u a website that does this, if u want
Answer:
I think the output can be any numbers because you don't have the function to put -8 in, so I can't identify the output exactly is.
Step-by-step explanation:
Answer:
Step-by-step explanation:
Answer:
a. 5
b. -3
Step-by-step explanation:
a. (5*(8^1/3 + 27^1/3)^3)^1/4
= ((40^1/3 + 135^1/3)^3)^1/4
≈ ((3.42 + 5.13)^3)^1/4
≈ (8.55^3)^1/4
≈ 625^4
= 5
b. 64^-1/3*(64^1/3 - 64^2/3)
= 0.25*(4 - 16)
= 1/4 or 0.25 *-12
= -12*1 / 4
= -12/4
= -3
Hope this helped :3